Implementation of the International Patient Safety Goals in Efforts to Reduce the Risk of Patient Falls in Hospitals: A Behavioral Perspective - Indriyani Indriyani; Zahroh Shaluhiyah; Daru Lestantyo (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
According to the World Health Organization (WHO), approximately 134 million adverse events occur annually in hospitals in low- and middle-income countries, contributing to an estimated 2.6 million deaths. Patient falls remain one of the most frequent preventable safety incidents in hospital settings. This study aimed to analyze behavioral and organizational factors influencing nurses in implementing the International Patient Safety Goals (IPSG), particularly in fall risk prevention. A quantitative cross-sectional design was employed. The study population consisted of 1,125 nurses at Hospital X, and 290 nurses were selected as the research sample using proportionate stratified random sampling based on the Lemeshow formula. Data were analyzed using Chi-square and multiple logistic regression tests. The results showed significant associations (p < 0.05) between knowledge, attitude, facilities and infrastructure, regulations, coworker support, leadership support, and IPSG implementation. A total of 63.8% of nurses demonstrated good IPSG implementation. Multivariate analysis identified facilities and infrastructure as the most dominant factor (p = 0.0001; OR = 4.562; 95% CI = 2.289–9.094), indicating that adequate facilities increased the likelihood of proper IPSG implementation by 4.562 times compared to inadequate facilities. In conclusion, strengthening structural readiness particularly ensuring adequate safety facilities is essential to improve IPSG implementation in fall risk prevention. However, the cross-sectional design limits causal interpretation, and self-reported data may not fully reflect actual clinical practice Keywords: International Patient Safety Goals Implementation, Fall Risk, Nurse Behaviour